The political message of non-politician presidential candidates: A framework for analysis. Issue 1 (1st July 2019) - Mjelde, Hilmar
Donald J. Trump's unlikely ascension to the US presidency has highlighted the scholarly need to study the political messaging of non-politician presidential candidates, as his successful run seems likely to inspire additional non-politicians to launch presidential bids in the future, both in the United States and in other polities, with unforeseeable consequences for political messaging ‐ particularly the limits of what is permissible political speech, the electoral process and voter representation. This article makes a contribution to filling this gap that exists in the literature by developing a framework for analysing the political message of non-politician presidential candidates. While the article focuses on non-politician presidential candidates in the United States, the theory it develops is general and should be applicable or adaptable to other presidential, and possibly non-presidential, regimes as well.